Stress Engineering Challenges in Mega Liquefied Natural Gas Projects: A Comprehensive Framework for Cryogenic System Design and Risk Mitigation - Ravi Pelodia (International Journal of Computational and Experimental Science and Engineering, 2026)
The mega onshore liquefied natural gas plants are larger than previous liquefied natural gas plants, and they involve different stresses. Therefore, a article is needed in order to provide risk analysis for satisfactory and safe operation. These high level of loadings and interactions between the imposed thermal contraction due to the cryogenic conditions lead to very high stress concentrations. The nonlinear material behavior in cryogenic conditions is very important for the distribution of these stresses through large piping systems. The design of cryogenic piping systems, which must deal with differential contraction, accepts piping flexibility. For the protection of equipment, critical nozzle loads, i.e. loads at pipe nozzles arising from equipment, must be defined. A support philosophy must therefore accommodate both the restraint and thermal effects. 3-dimensional stress analysis can be used to resolve the various loadings and complex geometries which require consideration in a mega scale plant. Risk assessment methodologies, design factor selection and reliability centered maintenance programs contribute to lowering the risk of anchor point failure leading to catastrophic stress failure, nozzle overload, and supporting structural failure. The interface management between modularized construction and stick-built construction methodologies, and the understanding of how construction sequences impact operational load profiles in mega LNG facilities contribute to the safety margins and operational reliability.